1997
DOI: 10.1099/00221287-143-12-3933
|View full text |Cite
|
Sign up to set email alerts
|

Functional redundancy of genes for sulphate activation enzymes in Rhizobium sp. BR816

Abstract: The broad-host-range, heat-tolerant Rhizobium strain BR816 produces sulphated Nod metabolites. Two ORFs highly homologous to the Sinorhizo&ium meliloti nodPQ genes were isolated and sequenced. It was found that Rhizo&ium sp. BR816 contained two copies of these genes; one copy was localized on the symbiotic plasmid, the other on the megaplasmid. Both nodP genes were interrupted by insertion of antibiotic resistance cassettes, thus constructing a double nodPlP2 mutant strain. However, no detectable differences i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
20
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 62 publications
1
20
0
Order By: Relevance
“…DNA fragments were recovered from agarose gels by using the Nucleotrap kit (MachereyNagel). Southern blotting and hybridizations were carried out as previously described (25). Sequencing of DNA fragments cloned in the pUC18-pUC19 vectors was performed on an automated ALF sequencer with fluorescein-labeled universal and synthetic oligonucleotide primers (Amersham Pharmacia Biotech, Uppsala, Sweden).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…DNA fragments were recovered from agarose gels by using the Nucleotrap kit (MachereyNagel). Southern blotting and hybridizations were carried out as previously described (25). Sequencing of DNA fragments cloned in the pUC18-pUC19 vectors was performed on an automated ALF sequencer with fluorescein-labeled universal and synthetic oligonucleotide primers (Amersham Pharmacia Biotech, Uppsala, Sweden).…”
Section: Methodsmentioning
confidence: 99%
“…strain BR816 possesses two nodPQ copies. Although both copies are functional, as demonstrated by genetic complementation of an R. tropici nodP mutant, the double mutants did not show any detectable changes in the amount of sulfated Nod factors produced by this strain (25). It was suggested that in Sinorhizobium sp.…”
mentioning
confidence: 92%
See 2 more Smart Citations
“…Quantitative analysis of GUS A activity was then carried out with p-nitrophenyl-ß-D-glucuronide (pNPG) as the substrate in microtiter plates and GUS A activity was examined in VERSA max microplate reader (Molecular Devices). To determination of Nod factors profile, the nodulation factors were radioactively labelled and they were isolated by following a slightly modified protocol of (Laeremans et al, 1998). 100μL from Bradyrhizobium cultures, growth for two nights, were inoculated in 900μL of each fresh culture medium and the concentration was adjusted to 5x10 8 CFU per medium milliliter.…”
Section: The Culture Media In Nod Factors Inductionmentioning
confidence: 99%